Studies on Soil Profiles in Chakrata Division of Uttar Pradesh - Yadav, J. S. P. (Indian Forester, 1963)
The paper deals with the study of 9 typical soil profiles examined under different forest crops occurring in Himalayas of Chakrata Forest Division of Uttar Pradesh. The climate and vegetation have been described and correlated with site features and morphological characteristics together with analytical data on important physical and chemical properties of the soil profiles. The data reveal that the soils are the product of long continued leaching under moist temperate climate and show fairly strong differentiation into A and B horizons. They are, in general, moderately deep, acidic in reaction, somewhat heavy in texture, non-calcareous in nature and have high content of organic matter, nitrogen, manganese and exchangeable calcium at the top. They are characterised by high water holding capacity, moderate to high nutrient retaining power and thin Aoo and Ao layers. As a result of local site features the soils of different forest communities show wide variation in many characters and profile development. The soils occupied by silver fir, spruce and kharsu oak at higher altitudes exhibit greater degree of podsolisation as compared to those dominated by ban oak (Q. incana) and moru oak (Q. dilatata) at lower elevations. The former soils are designated as weak podsolic, whereas the latter belong primarily to the brown forest soil group. The soils of conifers have comparatively lower pH but higher amount of organic matter and nitrogen at the top and greater dispersion of manganese in the profile than those under oaks, especially ban and moru oaks. Apart from heavy texture, accumulation of organic matter, high amount of manganese and restricted nutrient availability, excessive grazing is largely responsible for deficient natural regeneration of the species, in particular of conifers.